Competitiveness Partnerships : Building And Maintaining Public-Private Dialogue To Improve The Investment Climate - A Resource Drawn From The Review of 40 Countries ' Experiences - Herzberg, Benjamin (The World Bank, 2005)
The authors examine competitiveness partnerships, which consist of structured dialogue between the public and private sector to improve the investment climate. The paper is designed to be used as a resource by donors, governments, or businesspeople who are interested in establishing, maintaining, or improving a competitiveness partnership in their country or region. The political and economic context of a country determines the kind of partnership that is feasible and likely to succeed, and there is no one-size-fits-all approach. But it is possible to distill some ideas and techniques from best practice as many public-private dialogue mechanisms face similar challenges. Drawing on the experiences of 40 countries, the authors make a positive case for building and maintaining competitiveness partnerships, and offer a selection of valuable insights into how practitioners can design them so as to avoid common pitfalls. They demonstrate that reforms that are designed through public-private dialogue are better conceived and more effectively implemented because they arise from increased mutual understanding between government and the business community. The paper has three parts. Part One outlines what competitiveness partnerships can achieve. Part Two describes how competitiveness partnerships function, presenting issues to consider when designing such partnerships and a range of ways in which they may be approached. Part Three identifies challenges that competitiveness partnerships have frequently faced and strategies that have been used to overcome them